The Influence of Using Flashcard Media on Understanding the Content of Al-Qur'an Verses in Al-Qur'an Hadith Subjects - Putri Nur Lailatun Ni’mah; Sholikah (Konsultan Jurnal Ilmiah Indonesia, 2025)
This study aims to determine the effect of using flashcard media on students’ understanding of the content of Qur’anic verses in the Al-Qur’an Hadith subject. The background of this research is based on the low level of students’ understanding of the meanings and messages of Qur’anic verses due to the use of conventional teaching methods. This research employed a quantitative approach using an experimental method. The research subjects consisted of 20 students. Data were collected through Likert-scale questionnaires and comprehension tests. The data were analyzed using descriptive and inferential statistical analysis to identify the effect of flashcard media on students’ understanding. The results indicate that the use of flashcard media has a positive and significant effect on students’ understanding of the content of Qur’anic verses. Flashcards help increase learning interest, facilitate comprehension of verse meanings, and improve students’ ability to remember the content effectively. Therefore, flashcard media can be considered an effective alternative learning medium in the teaching of Al-Qur’an Hadith.